MODEL PERMAINAN BAR BAR UNTUK PENINGKATAN KETERAMPILAN GERAK DASAR PENCAK SILAT ANAK USIA 7-12 TAHUN - Febrianti Sugiharto , Ayu; Sri Rejeki, Hendriana; Bulubaan , Addriana (JURNAL ILMU KEOLAHRAGAAN, 2024)
This research aims to determine the feasibility and effectiveness of the BAR BAR game model guidebook for improving the basic pencak silat movement skills of children aged 7-12 years in Palu City. Adapting the research and development model of Borg & Gall using 7 (seven) development steps, the stages include ((1) preliminary study, (2) planning, (3) drafting, (4) expert validation, (5) small-scale trials , (6) large-scale trials, and (7) final product. A small-scale trial was carried out at the Pencak Sport Madani Sports Club martial art with 10 children aged 7-12 years. Large-scale trials were carried out at Tapak Naga Martial Art and Persaudaraan Setia Hati Terate with test subjects of 20 children aged 7-12 years. Operational field tests were carried out at the Persinas ASAD Martial Art, Tapak Suci Martial Art, and Tadulako Martial Art with 30 children aged 7-12 years and 9 coaches. The instruments used to collect data were interviews, questionnaires assessing basic pencak silat movement skills, observation questionnaires on game model development, observation questionnaires on the effectiveness of game model guidebooks, assessment questionnaires for media experts, game experts and pencak silat material experts as well as pretest posttest evaluation questionnaires for aged children. 7-12 years. The results of this research are in the form of a guidebook for the BAR BAR game model, consisting of 4 types of game models, namely: (1) the barricade game model, (2) the capture the flag game model, (3) the rope pulling game model and (4) the grab the pole game model. Based on the assessment of material experts, media and game experts, it can be concluded that the BAR BAR game model guidebook for improving basic pencak silat movement skills for children aged 7-12 years which has been prepared is very worthy and effective, so this BAR BAR game model guidebook is suitable for use. improving basic pencak silat movement skills for children aged 7-12 years